A high-contrast search for variability in HR 8799bc with VLT-SPHERE. Issue 1 (29th January 2021) - Biller, Beth A; Apai, Dániel; Bonnefoy, Mickaël; Desidera, Silvano; Gratton, Raffaele; Kasper, Markus; Kenworthy, Matthew; Lagrange, Anne-Marie; Lazzoni, Cecilia; Mesa, Dino; Vigan, Arthur; Wagner, Kevin; et al.
ABSTRACT: The planets HR8799bc display nearly identical colours and spectra as variable young exoplanet analogs such as VHS 1256-1257ABb and PSO J318.5-22, and are likely to be similarly variable. Here we present results from a 5-epoch SPHERE IRDIS broadband- H search for variability in these two planets. HR 8799b aperture photometry and HR 8799bc negative simulated planet photometry share similar trends within uncertainties. Satellite spot lightcurves share the same trends as the planet lightcurves in the August 2018 epochs, but diverge in the October 2017 epochs. We consider Δ( mag ) b − Δ( mag ) c to trace non-shared variations between the two planets, and rule out non-shared variability in Δ( mag ) b − Δ( mag ) c to the 10–20 per cent level over 4–5 h. To quantify our sensitivity to variability, we simulate variable lightcurves by inserting and retrieving a suite of simulated planets at similar radii from the star as HR 8799bc, but offset in position angle. For HR 8799b, for periods <10 h, we are sensitive to variability with amplitude 5 per cent . For HR 8799c, our sensitivity is limited to variability 25 per cent for similar periods.